PENGEMBANGAN E-LKPD IPA DI SD BERBASIS HOTS DENGAN PENDEKATAN TPACK PADA MATERI PERUBAHAN WUJUD BENDA MENGGUNAKAN LIVE WORKSHEETS DI SEKOLAH DASAR - Syifani, Ananda Aulia; Andriana, Encep; Hendracipta, Nana (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aimed to develop an electronic student worksheet (E-LKPD) based on Higher Order Thinking Skills (HOTS) using the Technological Pedagogical Content Knowledge (TPACK) approach on the topic of changes in the states of matter in elementary schools. The development utilized the Live Worksheets platform to create interactive worksheets that support students’ critical thinking, creativity, and problem-solving skills. The research employed a Research and Development (R&D) method following the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The E-LKPD product was validated by material and media experts, and its practicality and effectiveness were tested in a fifth-grade class at SDN Serang 11. The results indicate that the developed E-LKPD is valid, practical, and effective in enhancing students’ higher-order thinking skills in science learning.